2004
DOI: 10.1182/blood-2003-08-2781
|View full text |Cite
|
Sign up to set email alerts
|

Kaposi sarcoma-associated herpesvirus (KSHV) induces heme oxygenase-1 expression and activity in KSHV-infected endothelial cells

Abstract: IntroductionKaposi sarcoma-associated herpesvirus (KSHV; also human herpesvirus-8) is implicated in all clinical forms of KS 1,2 as well as the lymphoproliferative disorders primary effusion lymphoma (PEL) 3,4 and multicentric Castleman disease (MCD). 5 Endothelial cells harbor the KSHV genome in vivo, 1,6,7 are permissive for virus infection in vitro, [8][9][10][11] and are thought to be the precursors of spindle cells. [12][13][14][15] We and others have shown that in vitro infection of human dermal microvas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
70
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 76 publications
(75 citation statements)
references
References 60 publications
5
70
0
Order By: Relevance
“…The IR joins a growing list of host cell proteins essential for the transformed phenotype in ECs infected by KSHV in vitro (Moses et al, 2002;McAllister et al, 2004;Raggo et al, 2005). It seems that multiple mechanisms are required to support the postconfluent growth of DMVEC.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The IR joins a growing list of host cell proteins essential for the transformed phenotype in ECs infected by KSHV in vitro (Moses et al, 2002;McAllister et al, 2004;Raggo et al, 2005). It seems that multiple mechanisms are required to support the postconfluent growth of DMVEC.…”
Section: Discussionmentioning
confidence: 99%
“…Upon infection with KSHV, E-DMVECs develop a spindle cell phenotype, lose contact inhibition, form foci when cultured postconfluence and acquire the ability to form colonies in soft agar. The E-DMVEC system has thus been extremely useful for evaluating changes in the cellular transcriptome and proteome, ultimately leading to the identification of both known as well as novel oncogenes that are likely to be involved in KS tumorigenesis (Moses et al, 2002;McAllister et al, 2004;Raggo et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, a recent study has shown that HO-1 expression and activity are induced by an angiogenic oncovirus, the Kaposi sarcoma-associated herpesvirus (KSHV), in endothelial cells. Besides, elevated levels of the enzyme are detectable in biopsy tissue from oral AIDS-Kaposi sarcoma lesions (12).…”
mentioning
confidence: 99%
“…Suppression of RDC1 and neuritin gene expression by antisense oligonucleotides or siRNA reversed the morphological changes and increased proliferation induced by KSHV in DMVECs and also the growth in soft agar and tumourigenicity in the nude mouse model of 3T3 mouse fibroblasts stably transfected with either RDC1 or neuritin [80]. Haem oxygenase 1 (HO-1) is among several other cellular genes induced in cultured endothelial cells by latent KSHV infection [78][79][80][81][82][83] and is also expressed in KSHV-infected spindle cells in KS lesions [83]. The HO-1 inhibitor chromium mesoporphyrin IX inhibits haem-induced proliferation of KSHV-infected, but not uninfected, DMVECs, suggesting a role for HO-1 in the proliferation of KSHV-infected spindle cells [83].…”
Section: The Role Of Kshv In the Development Of Kaposi's Sarcomamentioning
confidence: 99%
“…Haem oxygenase 1 (HO-1) is among several other cellular genes induced in cultured endothelial cells by latent KSHV infection [78][79][80][81][82][83] and is also expressed in KSHV-infected spindle cells in KS lesions [83]. The HO-1 inhibitor chromium mesoporphyrin IX inhibits haem-induced proliferation of KSHV-infected, but not uninfected, DMVECs, suggesting a role for HO-1 in the proliferation of KSHV-infected spindle cells [83]. It is likely that other KSHV-induced cellular genes also contribute to the development of KS spindle cells.…”
Section: The Role Of Kshv In the Development Of Kaposi's Sarcomamentioning
confidence: 99%